KAJIAN SIFAT FISIK, KIMIA DAN FISIOLOGI TERHADAP BEBERAPA TINGKAT KEMATANGAN BUAH RAMBUTAN VARIETAS SI MACAN DI KABUPATEN GUNUNG KIDUL YOGYAKARTA - Nurhayati, Siti (Jurnal Matematika Sains dan Teknologi, 2004)
The aim of this research was to determine theee effect of physical, chemical and physiological characteristic of several stages maturity of rambutan cultivar Simacan in Wonosari, Gunung Kidul, Yogyakarta. This experimental research was conducted from March to May 2004 used a single factorial Randomized Complete Design (RCD), consisted of six levels, i.e.: A (Rambutan fruit with red stages of maturity), B (Rambutan fruit with yellowness red stages of  maturity), C (Rambutan fruit with yellow  stages of  maturity),  D (Rambutan fruit with greennes  yellow stages of  maturity), E (Rambutan fruit with green  stages of  maturity).  The treatment was done in three replications. The research result showed that (i) According to the physical characteristics (weight of whole fruit, fruit flesh and flesh thickness), rambutan in red stages of maturity (84,340%), the highest sugar content was in the red stages of maturity (86,20%), the highest vitamin C content was in the red stages of maturity (29,151%) and the highest total solution soluble was in the yellow stages of maturity (15,104%) (iii). According to the physiological characteristics, the highest respiration rate was in the greenness yellow fruits stage of maturity ( 0,0495%). Based on the research, it is better for  farmers to harvest rambutan Simacan once they are in red stage. In this stage the rambutan will have its highest sugar, and vitamin C contents.